THE EFFECT OF GROUP COUNSELING SERVICES USING BEHAVIORAL REHEARSAL TECHNIQUES ON SPEAKING ANXIETY IN CLASS VII B STUDENTS OF SMP N 17 BENGKULU CITY: Pengaruh Layanan Konseling Kelompok Dengan Teknik Behavioral Rehearsal Terhadap Kecemasan Berbicara Pada Peserta Didik Kelas VII B SMP N 17 Kota Bengkulu - Naufal Rahman Hadi; Anni Suprapti; Arsyadani Mishbahuddin (UNIVERSITAS BENGKULU, 2025)
This research aims to describe the effect of group counseling services using behavioral rehearsal techniques on speaking anxiety of class VII B students at SMPN 17 Bengkulu City. This research method uses an experimental one group pretest posttest design method. The population in this study was class VII B students, totaling 29 students. The research sample was taken using a purposive sampling technique with a sample size of 5 students with high levels of speaking anxiety. The data collection technique uses a questionnaire with a Likert scale with research data analysis techniques using a paired sample t-test. The results obtained in the research showed that before being given behavioral rehearsal technique group counseling services, students' speaking anxiety levels were in the high category and after being given behavioral rehearsal technique group counseling services, students' speaking anxiety levels were in the low category. There is a difference in speaking anxiety between before and after being given group counseling services using behavioral rehearsal techniques, which means that there is an influence of group counseling services using behavioral rehearsal techniques on speaking anxiety of class VII B students at SMP N 17 Bengkulu City. Keywords: speaking anxiety, group counseling, behavioral rehearsal